2022
DOI: 10.1159/000526155
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Pathologic Complete Remission in Patients with Hormone Receptor-Positive and Human Epidermal Growth Factor Receptor 2-Negative Breast Cancer Receiving Neoadjuvant Chemotherapy

Abstract: <b><i>Introduction:</i></b> Pathological complete response (pCR) after neoadjuvant chemotherapy (NAC) is associated with improvement in survival outcomes. This study evaluated the pCR in patients with hormone receptor (HR)-positive and human epidermal growth factor receptor 2 (HER2)-negative breast cancer after NAC. <b><i>Methods:</i></b> We evaluated 417 patients who were diagnosed with invasive breast cancer and treated with NAC followed by curative surgery bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…On the other hand, concordant with our findings, they also found that high Ki-67 level was significantly associated with more pCR in HR+/HER2- BC patients. In a large retrospective study, patients with tumors having single (either ER or PR) HR-positivity, and high Ki-67 expression had higher pCR rates than those with both ER and PR positivity and low Ki-67 expression [21]. Studies provided that increasing the threshold of high Ki-67 expression by over 30% resulted in more pCR in patients with ER+/HER2- BC [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, concordant with our findings, they also found that high Ki-67 level was significantly associated with more pCR in HR+/HER2- BC patients. In a large retrospective study, patients with tumors having single (either ER or PR) HR-positivity, and high Ki-67 expression had higher pCR rates than those with both ER and PR positivity and low Ki-67 expression [21]. Studies provided that increasing the threshold of high Ki-67 expression by over 30% resulted in more pCR in patients with ER+/HER2- BC [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…(2017), в котором высокий уровень Ki67 до начала терапии был ассоциирован с лучшим ответом на НАХТ в отношении полной патоморфологической ремиссии, причем оптимальным cut-off авторы считают 15-20 %, отмечая существенную гетерогенность пороговых уровней в разных исследованиях (от 14 до 50 %) [49]. Сходные результаты в отношении прогностической значимости Ki67 при химиотерапии показаны и в более поздних исследованиях, где пороговое значение находилось в диапазоне от 14 % до 20 % [50][51][52][53]. Кроме того, подтверждено прогностическое значение оценки уровня Ki67 после НАХТ в послеоперационных образцах [54,55].…”
Section: Introductionunclassified